STRATEGIES FOR HALAL TOURISM IN SOUTH KOREA TO ATTRACT MUSLIM TOURISTS IN SOUTHEAST ASIA - Umi Larasati; Fuad Buntoro; Heni Verawati (JURNAL MANAJEMEN DAKWAH, 2025)
The halal lifestyle trend is growing, with non-Muslim countries beginning to brand themselves as Muslim-friendly countries, including South Korea. However, there are still not many studies that discuss this issue in depth. Many new studies focus solely on strategies to attract tourists in Muslim-majority countries. The purpose of this study is to analyze the collaboration between the government, organizations, and cultural diplomacy as effective strategies for increasing Muslim tourist visits. The research method used is a literature study. The results show that collaboration among the government, the Korea Tour Organization, the Korea Muslim Federation, and cultural diplomacy significantly increases Muslim tourists' interest in visiting. This study also demonstrates that collaboration among various parties is a strategy that significantly influences tourist interest and strengthens the position of halal tourism destinations worldwide.